Personnel management in the University of the Philippines - Frago, Pio P. (1983)
Structures and processes involved in managing the human resource of the University (i.e., faculty; research, extension and professional staff; and administrative staff) such as recruitment and selection, appointment, promotion, tenure, compensation and benefits, are described to show the complexity of administering the University. With the creation of the Human Resource Development Office (HRDO), the personnel operations of the University were streamlined to make it more responsive to the needs of the University and society as a whole. Still, problems are foreseen because of the continuing growth and expansion of the University, and solutions to these are recommended.
Keywords: Personnel management; Human Resource Development (HRD); Employee selection; University of the Philippines System